PENGARUH PELATIHAN EMOTIONAL INTELLIGENCE TERHADAP PERILAKU CARING PENGASUH ANAK - Gabriella Hana Khosasih; Hartanti Hartanti; Ktut Dianovinina (Perpustakaan Universitas Surabaya, 2018)
The aim of this study is to see the impact of emotional intelligence (EI) training on babysitter’s caring behavior. The research aproach uses convergent parallel mixed methods design Quantitative reaserch used one group pretest and posttest experimental design and qualitative research used fenomenology paradigm to understand babysitter’s experience. Participant in this study is a female and a woman who have low caring behavior competence and EI competence. Assessment in this study used behavior based interview to identify competence level of each participants. Five sessions of EI training were implemented in three days. Follow up was held three days after training. Level competence of caring behavior and emotional intelliegence are increase after training. There’s also a increase in each participant’s knowledge of emotional intelligence. The result of this study may indicate that emotional intelligence training could be one alternative to increase babysitter’s caring behavior.